Use of ß-tricalciumphosphate in the composition of granules in treatment of long-bone fractures - Shymon, Vasyl; Meklesh, Yurii; Alfeldii, Sergii; Stoika, Vasyl; Kochmar, Vitalii (ScienceRise: Medical Science, 2020)
A promising direction in the treatment of bone defects in traumas and tumours is a method of using materials to replace a bone defect based on ß-tricalcium phosphate ceramics and bioglass. The aim: to analyse the results of surgical treatment in patients with bone defect replacement by β-tricalcium phosphate granules and bioglass. Materials and methods: the results of treatment of 41 patients treated at the Department of Orthopedics of the ZOKL named after M.P. Novak from 2016 to 2019. Inclusion of patients in the study suggested the presence of bone defects of traumatic or destructive origin. The patients were divided into three groups. They underwent surgery with osteosynthesis and plastics of bone defects with ß-tricalcium phosphate ceramics, and in four patients the defect was replaced with a bioglass. Results. The results of treatment were studied in 39 patients based on the criterion score. Two patients did not appear at the last clinical examination. The observation period was 1-1.5 years after surgery. In 43.59% of cases the results were good, 51.28% were satisfactory. In two patients, the results were unsatisfactory due to the fracture of the metal retainer. These patients underwent reosteosynthesis with re-filling of the defect. Conclusions. The use of ß-tricalcium phosphate for long bone defect plasticity improves treatment outcomes by stimulating reparative osteogenesis in the bone, which contributes to the restoration of limb function and the quality of life of patients. β-tricalcium phosphate granule ceramics is the gold standard in the treatment of long bone defects of traumatic and tumorous origin